Problem Based Learning Flipbook Media to Improve Students' Listening and Writing Skills - Dian Anggita, Desak Ayu Made; Nice Maylani Asril; Ni Ketut Desia Tristiantari (Universitas Pendidikan Ganesha, 2024)
The problem of this research focuses on the low listening and writing skills of descriptive texts from students due to student interest factors and teacher innovation in delivering learning materials. This condition requires a solution through the learning media and an innovative learning approach. This study aims to develop flipbook media based on the Problem-Based Learning model to improve listening and writing skills to influence student learning motivation. This type of research is developed using the ADDIE model. The study subjects were 2 learning design experts, 2 learning media experts, and 2 learning material experts. The subjects of the study involved 24 fourth-grade students. Data were collected using skill tests and writing descriptive texts as research instruments. Data analysis was conducted using inferential statistical tests, namely the t-test, to determine significant differences before and after implementing flipbook media. The study showed that flipbook media based on Problem-Based Learning received very good qualifications from experts. The results of the practicality test also showed that the media was very practical to use. The hypothesis test results showed that flipbook media based on Problem-Based Learning significantly improved students' listening and writing skills compared to conventional learning. It is concluded that applying flipbook media based on Problem-Based Learning effectively improves the listening and writing skills of descriptive texts students, which answers the problem of low listening and writing skills in descriptive texts. This study implies that teachers can use flipbook media based on Problem-Based Learning to improve listening and writing skills.